Meaning of the Elements of 'Commendable Attitudes and Actions' for Convicts as the Basis for Changing Death Penalties to Life Imprisonment Penalties Based on Law Number 1 of 2023 concerning the Criminal Code - Edward Septian Nugraha; Rahel Octora (PT Mattawang Mediatama Solution, 2023)
In the year 2023, Indonesian national code was legalized. Inside the new KUHP, there is a chapter 100 that regulates the decline of death penalty to life imprisonment on a 10 (ten) year probation that must qualify as “attitude and deed”. It can cause uncertainty about the law because to date there are no standards or standards used to judge attitudes and good deeds. Therefore, this article will discuss an analysis of the “attitude and good deed” of the penal code as the basis for death penalty to life imprisonment and the law enforcement analysis of the conditions of attitude and good deed in article 100 of penal law 2023. The study was a normative-juridicial investigation that centered on regulations of legislation, principles and laws, The data he’s using is. Primary law and secondary law material. Therefore, the study results in the implemantation of attitude and commendable actions must be explained in detail and governments must establish executive regulations against reducing death penalty to life imprisonment in order to ensure legal certainty.